Evaluasi Prestasi Akademik Siswa: Sebuah Tinjauan Terhadap Keterlibatan Orang Tua dalam Pendidikan - Taufik Hidayat Siregar; Friyatmi (Universitas Negeri Padang, 2025)
This study aims to analyze the contribution or effects of parental involvement on students academic achievement. Using a quantitative associative approach with a sample of 166 students. Data was collected through questionnaires and documentation. The results reveal a positive and significant influence of parental involvement on the academic achievement of students at SMAN 8 Padangsidimpuan. This suggests that improving parental involvement leads to better academic outcomes for students